Future Directions of the Ministry of Higher Education. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2004)

(untitled)
Following the cabinet reshuffle this year, the Ministry of Higher Education was established on 27th March 2004. The Ministry consists of Public Institutions of Higher Learning, Private Higher Educational Institutions, Polytechnics, Community Colleges and University Colleges.